Healthcare Access Regional Overviews - Bacha, Umar; Rozman, Urška; Šostar Turk, Sonja (IntechOpen, 2020)
Healthcare Access - Regional Overviews is a compilation of ten chapters consisting of case studies, research works, reviews, and expert opinions providing insight on the previous and current developments in the field of hygiene and infection control with practices to prevent or minimize the spread of infectious diseases. The book also addresses the status and healthcare access of the most neglected segments in less developed countries. All chapters are written by global researchers are edited by experts in the field. The information presented in this work can be replicated at different levels to accelerate timely and quality healthcare services.